Prevalence and Plasmid Profiles of Enterobacteriaceae Isolates Obtained from Individuals with Asymptomatic Bacteriuria in Okada, Edo State, Nigeria - Otote, Osarumwense Precious; Okwu, Maureen Uchechukwu; Izevbuwa, Osazee Ekundayo; Oferiofe, Happy Ovuerhi (UI Scholars Hub, 2022)
Asymptomatic bacteriuria (ASB) is the presence of bacteria in apparently healthy individuals. Although, the prevalence varies widely with age, gender, and the presence or absence of genitourinary abnormalities, the detection of pathogenic bacteria in urine constitutes firm evidence of infection. The objectives of this study were to isolate members of the family Enterobacteriaceae from urine samples of research participants, and to determine the antibacterial susceptibility and plasmid profiles of the isolates. A total of 122 mid-stream urine samples consisting of 72 male and 50 female participants from selected primary and secondary schools were collected. The age of the participants used in this study ranged between 4 years to 19 years old. Isolates were cultured on MacConkey agar and Cysteine lactose electrolyte deficient agar and then incubated for 24 hr at 37 °C. The overnight culture was then subjected to antibiotic susceptibility testing using the disk diffusion test as described by Kirby-Bauer. Thereafter, plasmid analysis was carried out. The statistical package used to analyze the samples was IBM SPSS v23 to cover the calculations for the chi-square, student t-test, and analysis of variance. The frequency of bacterial isolates with respect to age were obtained, as follows: 4–8 (9.0%), 9–13 (16.4%), 14–18 (2.5%) and >19 (1.6%). The prevalence of the four (23; 63.9%) Enterobacteriaceae isolate groups were: Escherichia coli (36.1%), Citrobacter species (11.1%), Klebsiella species (8.3%) and Enterobacter species (8.3%) while non Enterobacteriaceae (13) was 36.1%. A prevalence of 25.9% of ASB was reported in this study where the percentage occurrence of bacteria isolates showed high prevalence in the male participants, at 17.2% compared to the 12.3% reported for the female participants. The antibiogram showed that all isolates were susceptible to Cefprozil except isolates belonging Klebsiella species that showed resistance to the antibiotic. Citrobacter species and Klebsiella species isolates were susceptible to Ofloxacin while Enterobacter species isolates was only susceptible to Cefixime. The percentage figures from resistant plasmid profile analysis indicated that Cefuroxime, Cefprozil and Ofloxacin showed relatively good susceptibility profile against the nine bacterial isolates that were subjected to the analysis. Resistance After plasmid curing was majorly chromosomally-borne. From this research, the prevalence of ASB was found yo be high in Okada, with the infection being higher in males having Escherichia coli as the commonest bacterial isolate. Hence, there is need for early routine evaluation as well as detection of this silent infection for prompt referral and intervention.